Enhancing efficiency and stability in CPT systems: a state feedback controller approach - Al-Hattami, Ahmed; Saat, Shakir; Yusop, Yusmarnita; Awal, Md Rabiul; Shapri, A. H. M.; Husin, Huzaimah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This work aims to present an innovative design and simulation of an auto-tuning capacitive power transfer (CPT) system. The system utilizes a Class-E converter, renowned for its exceptional efficiency. Challenges arise when trying to regulate the output voltage of a Class-E converter in the presence of load fluctuations, leading to an escalation in switching losses. By employing first harmonic approximation (FHA) and generalized state space averaging (GSSA), a state-space model of the system is constructed to effectively address this problem. The output voltage is regulated by a state feedback controller developed using the Lyapunov approach. This paper presents a comparative analysis of a traditional PID controller and a recently suggested state feedback controller, with a primary emphasis on system stabilization. The study examines the similarities and differences between the two controllers. The efficacy of the proposed controller design is demonstrated through the utilization of simulation data. Furthermore, these results confirm the validity of the comparative study, making it a substantial contribution to the field of CPT systems.